Folk medicine in the northern coast of Colombia: an overview - Medina José; Guzmán-Ledezma Jaime; Mercado-Camargo Jairo; Franco-Ospina Luís; Díaz-Castillo Fredyc; Gómez-Estrada Harold; Gaitán-Ibarra Ricardo (BMC, 2011)
Abstract Background Traditional remedies are an integral part of Colombian culture. Here we present the results of a three-year study of ethnopharmacology and folk-medicine use among the population of the Atlantic Coast of Colombia, specifically in department of Bolívar. We collected information related to different herbal medicinal uses of the local flora in the treatment of the most common human diseases and health disorders in the area, and determined the relative importance of the species surveyed. Methods Data on the use of medicinal plants were collected using structured interviews and through observations and conversations with local communities. A total of 1225 participants were interviewed. Results Approximately 30 uses were reported for plants in traditional medicine. The plant species with the highest fidelity level (Fl) were Crescentia cujete L. (flu), Eucalyptus globulus Labill. (flu and cough), Euphorbia tithymaloides L. (inflammation), Gliricidia_sepium_(Jacq.) Kunth (pruritic ailments), Heliotropium indicum L. (intestinal parasites) Malachra alceifolia Jacq. (inflammation), Matricaria chamomilla L. (colic) Mentha sativa L. (nervousness), Momordica charantia L. (intestinal parasites), Origanum vulgare L. (earache), Plantago major L. (inflammation) and Terminalia catappa L. (inflammation). The most frequent ailments reported were skin affections, inflammation of the respiratory tract, and gastro-intestinal disorders. The majority of the remedies were prepared from freshly collected plant material from the wild and from a single species only. The preparation of remedies included boiling infusions, extraction of fresh or dry whole plants, leaves, flowers, roots, fruits, and seeds. The parts of the plants most frequently used were the leaves. In this study were identified 39 plant species, which belong to 26 families. There was a high degree of consensus from informants on the medical indications of the different species. Conclusions This study presents new research efforts and perspectives on the search for new drugs based on local uses of medicinal plants. It also sheds light on the dependence of rural communities in Colombia on medicinal plants.